A pre‐Miocene Irano‐Turanian cradle: Origin and diversification of the species‐rich monocot genus Gagea (Liliaceae). Issue 10 (26th April 2019) - Peterson, Angela; Harpke, Dörte; Peterson, Jens; Harpke, Alexander; Peruzzi, Lorenzo
Abstract: The Irano‐Turanian (IT) floristic region is considered an important center of origin for many taxa. However, there is a lack of studies dealing with typical IT genera that also occur in neighboring areas. The species‐rich monocot genus Gagea Salisb. shows a center of diversity in IT region and a distribution in adjacent regions, therefore representing a good study object to investigate spatial and temporal relationships among IT region and its neighboring areas (East Asia, Euro‐Siberia, Himalaya, and Mediterranean). We aimed at (a) testing the origin of the genus and of its major lineages in the IT region, (b) reconstructing divergence times, and (c) reconstructing colonization events. To address these problems, sequences of the ribosomal DNA internal transcribed spacer (ITS) region of 418 individuals and chloroplast intergenic spacers sequences ( psb A‐ trn H, trn L‐ trn F) of 497 individuals, representing 116 species from all sections of the genus and nearly its entire distribution area were analyzed. Divergence times were estimated under a random molecular clock based on nrITS phylogeny, which was the most complete data set regarding the representation of species and distribution areas. Ancestral distribution ranges were estimated for the nrITS data set as well as for a combined data set, revealing that Gagea most likely originated in southwestern Asia. This genus first diversified there starting in the Early Miocene. In the Middle Miocene, Gagea migrated to the Mediterranean and to East Asia, while migration into Euro‐Siberia took place in the Late Miocene. During the Pleistocene, the Arctic was colonized and Gagea serotina, the most widespread species, reached North America. The Mediterranean basin was colonized multiple times from southwestern Asia or Euro‐Siberia. Most of the currently existing species originated during the last 3 Ma. Abstract : Divergence time estimation and ancestral range reconstructions were carried out for the species‐rich monocot genus Gagea (Liliaceae). Our study could demonstrate that the species‐rich Irano‐Turanian (IT) floristic region, a current centre of Gagea species diversity, is also the origin of the genus and of its major linages. Colonisation of adjacent areas started from the IT floristic region and benefit from periods of climatic changes creating dry habits. Therefore, our study supports that the IT region is an important source of taxa for adjacent areas of Euro‐Siberia.